New evidence for the influence of step morphology on the formation of Au atomic chains on vicinal Si(111) surfaces - MCGILP, JOHN (My University, 2010)
Gold atomic chain structures that grow on singular and vicinal Si(111) surfaces have attracted considerable interest as model systems for exploring quasi-one-dimensional metallic behaviour. The structure of the prototypical Si(111)-5 x 2-Au system remains controversial, however. Reflection anisotropy spectroscopy provides new, independent evidence supporting a recently proposed three-Au-chain structure. For stepped surfaces, the results provide good evidence that a single Au chain forms adjacent to [(1) over bar(1) over bar2] steps and a double Au chain forms adjacent to [11 (2) over bar] steps. In both cases spectral lineshape and coverage data support a three-chain Si(111)-5 x 2-Au structure forming over the remainder of the terrace. For all the vicinal Si(111) surfaces, including Si(557) and Si(775), it is the step morphology, and not the terrace width, that determines whether single- or double-Au-chain structures are formed in the region of the steps.
PUBLISHED
Keywords: Particles and fields physics; SI SURFACES; GOLD; Nanoscience & Materials